Ribonuclease T1 generates circular RNA molecules from viroid-specific RNA transcripts by cleavage and intramolecular ligation. - Tsagris, M (1991)
A 406 nucleotide long potato spindle tuber viroid (PSTVd)-specific linear RNA transcript was synthesized in vitro and subjected to limited digestion with ribonuclease (RNase) T1. Under certain conditions this guanosine-specific endoribonuclease proved to be capable of processing the longer-than-unit-length, precursor-like viroid RNA transcript by cleaving out a linear 358 nucleotide long product and ligating that to a circular RNA molecule. The new finding that RNase T1 acts as an RNA processing enzyme and, in particular, as an RNA 'circulase' can be explained by the unique structural preconditions inherent in the viroid-specific substrate and by the well characterized two-step cleavage mechanism of the enzyme. These in vitro potentials of RNase T1 suggest that also in vivo procaryotic and eucaryotic RNases with a similar reaction mechanism might not only be involved in RNA degradation and trimming, but also in processing, ligation and recombination of RNA.